Optimasi Parameter Permesinan Terhadap Tingkat Kekasaran Permukaan Aluminium Proses Pembubutan Dengan Metode Taguchi - Diki Ismail Permana; Yayat Yayat (Department of Mechanical Engineering, Universitas Andalas, 2019)
This study is to determine the most suitable machining parameters to produce optimum surface roughness on turning operations using the Hurco TM20 CNC machine, ISCAR DNMG IC907 insert tool with aluminum 6061 as an object test material. The analysis was carried out using the Taguchi method with objective functions smaller the better and using ANOVA (analysis of variance) that determines which machining parameters have a significant effect on surface roughness. The machining parameters that evaluated are spindle speed, feedrate, and depth of cut. The test results shows that the machining parameters that produce the optimal surface roughness level is on range of 0.28 ± 0.13, and the parameters are spindle speed = 2092 rpm, feedrate = 0.07 mm / ref, dept of cut = 0.5 mm.